A fatal groove - Blacke, Olivia (Blacke, Olivia. Record shop mysteries, 2023)
"It's springtime in Cedar River, Texas. Juni Jessup and her sisters Tansy and Maggie thought opening Sip & Spin Records was going to be their biggest hurdle, but the Frappuccino hits the fan when the mayor drops dead, poisoned by their delicious coffee. Juni will have to pull out all the stops to find the mayor's killer."--Back cover.